2014
DOI: 10.1371/journal.pone.0106707
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Metagenome Survey of the Fecal Microbiota of a Breast- and a Plant-Fed Asian Elephant Reveals an Unexpectedly High Diversity of Glycoside Hydrolase Family Enzymes

Abstract: A phylogenetic and metagenomic study of elephant feces samples (derived from a three-weeks-old and a six-years-old Asian elephant) was conducted in order to describe the microbiota inhabiting this large land-living animal. The microbial diversity was examined via 16S rRNA gene analysis. We generated more than 44,000 GS-FLX+454 reads for each animal. For the baby elephant, 380 operational taxonomic units (OTUs) were identified at 97% sequence identity level; in the six-years-old animal, close to 3,000 OTUs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 54 publications
8
97
1
Order By: Relevance
“…An enormous range of different habitats (Amore et al, 2013a) such as soil, compost, decaying plant materials (Zhang et al, 2006; Amore et al, 2013b), rumens (Dai et al, 2012), sewage sludge (Singh et al, 2011), termite guts (Warnecke et al, 2007), forest waste (Ventorino et al, 2013, 2016b), and wood processing plants (Dawkins and Esiobu, 2016), animal feces (Ilmberger et al, 2014), paper mills, and hot springs (López-López et al, 2013) have been so far investigated as sources of both aerobic and anaerobic bacteria producing several different enzymes of industrial interest. In particular, lignocellulosic biomass represents complex ecosystems in which environmental conditions influence living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…An enormous range of different habitats (Amore et al, 2013a) such as soil, compost, decaying plant materials (Zhang et al, 2006; Amore et al, 2013b), rumens (Dai et al, 2012), sewage sludge (Singh et al, 2011), termite guts (Warnecke et al, 2007), forest waste (Ventorino et al, 2013, 2016b), and wood processing plants (Dawkins and Esiobu, 2016), animal feces (Ilmberger et al, 2014), paper mills, and hot springs (López-López et al, 2013) have been so far investigated as sources of both aerobic and anaerobic bacteria producing several different enzymes of industrial interest. In particular, lignocellulosic biomass represents complex ecosystems in which environmental conditions influence living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Since their original isolation from the rumen, cultureindependent studies have suggested the presence of Fibrobacter populations in diverse herbivore gastrointestinal tracts (Lin and Stahl, 1995;Matsui et al, 2010;Ilmberger et al, 2014). However, cultured representatives from most of these hosts are rare, and as a result, our understanding of their physiology is limited.…”
Section: Introductionmentioning
confidence: 99%
“…GHH01 were employed. Accordingly, metagenomic DNAs from elephant feces (Ilmberger et al, ), a biogas reactor (Güllert et al, ), and a microalgae culture (Krohn‐Molt et al, ) as well as gDNAs from E. coli , Bacillus subtilis , Propionibacterium acidipropionici , Paenibacillus sp., and Picrophilus torridus were used as templates for further transcription assays. A commercial E. coli RNAP holoenzyme from New England Biolabs was used according to manufacturer's recommendations to compare transcription profiles.…”
Section: Methodsmentioning
confidence: 99%